Diseño y Modelado Cinemático de Exoesqueleto de Hombro para Paciente con Enfermedad Cerebrovascular - Ibarra-Zea, Edgar; Martínez Peón, Dulce Citlalli; Sosa Méndez, Deira (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Currently, there are people worldwide with motor disabilities due to cerebrovascular diseases. To face this problem, people are subjected to physiotherapies to help them recover the motor mobility of the upper limb, but currently, it is not possible to meet the high demand of people who require it. This gave rise to the development and use of exoskeletons to meet the high demand of patients, however, the problem with the exoskeletons currently positioned in the market is that they do not adapt to the anthropometry of the Mexican population. In the present work, we present the design of an exoskeleton to assist physical therapists in the motor rehabilitation of the shoulder for the Mexican population over 18 years old. This exoskeleton can perform the three basic shoulder movements (abduction-adduction, flexion-extension and internal-external rotation) and an extra movement is considered in the elbow part which is flexion-extension. In addition, kinematic modelling is presented, and use is made of MATLAB® software to visualize the movements of each joint.